THE CORRELATION BETWEEN KNOWLEDGE LEVEL ABOUT CIGARETTES AND PEER SUPPORT WITH SMOKING BEHAVIOR IN STUDENTS AT SMKS MATHLA’UL ANWAR BUARANJATI - Meliana Indhar Regita Cahya; Alif Nurul Rosyidah; Osep Yasier Almunsiri (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Background: Smoking is a serious health problem among adolescents due to the increasing number of novice smokers at school age. Smoking behavior in adolescents can be influenced by various factors, including the level of knowledge about smoking and peer support. Objective: This study aims to determine the relationship between the level of knowledge about smoking and peer support with smoking behavior in students at SMKS Mathla'ul Anwar Buaranjati. Method: This research method applies quantitative research with a cross-sectional approach. The population in this study was 103 students. Sampling used the Stratified Random sampling technique with a sample size of 90 respondents. The research instrument was a questionnaire. Results: The results of bivariate analysis using the Chi-Square test showed that there was a relationship between the level of knowledge with smoking behavior (p value = 0.037) and peer support with smoking behavior (p value = 0.025). Conclusion: There is a relationship between the level of knowledge and peer support with smoking behavior in students at SMKS Mathla'ul Anwar Buaranjati.